2017
DOI: 10.1128/jcm.00865-17
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antigenic Relatedness between GII.4 and GII.17 Noroviruses by Use of Serum Samples from Norovirus-Infected Patients

Abstract: A novel GII.17 norovirus variant caused major gastroenteritis epidemics in China in 2014 to 2016. To explore the host immune factors in selection of the emergence of this new variant, we characterized its antigenic relatedness with the GII.4 noroviruses that have dominated in China for decades. Through an enzyme-linked immunosorbent assay (ELISA) and a histo-blood group antigen (HBGA) blocking assay using sera from GII.4 and the GII.17 variant-infected patients, respectively, we observed limited cross-immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…3), indicating their evolutionary changes over time. These differences may contribute to the observed antigenic differences among different GII.17 variants (33), as well as those between GII.17 huNoVs and other GII genotypes (41).…”
Section: Resultsmentioning
confidence: 99%
“…3), indicating their evolutionary changes over time. These differences may contribute to the observed antigenic differences among different GII.17 variants (33), as well as those between GII.17 huNoVs and other GII genotypes (41).…”
Section: Resultsmentioning
confidence: 99%
“…The glycan binding profiles of huNoVs have been shown to be associated with their infection risk (3, 2429), and possibly also their prevalence (19, 21). We showed that the GII.13/21 huNoVs with the new GBS recognize a broad spectrum of terminal β-Gal-containing glycans, including mucin core 2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a new variant of the previously rare genotype GII.17 became the predominant strain to cause outbreaks during the epidemic season of 2014–2015 (17, 18). Along with the antigenic change (17), the new GII.17 variant had a broader HBGA binding spectrum due to minor mutations at the conserved GII glycan binding site (GBS) (1821). Therefore, identification of the new huNoV-glycan interactions, especially those of the rare genotypes, is necessary to help in the prevention and control of huNoV-associated diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, NV conferred immunity to a later challenge with the Montgomery County virus (GI.5), suggesting an antigenic relatedness between genotypes within a genogroup (112). However, it is not always the case since by measuring cross-reactivity and cross-blockade activity, using serum samples from HuNoV-infected patients, limited crossreactivity was found but no cross-blockade activity between GII.4 and GII.17, suggesting that GII.4-specific immunity does not provide efficient protection against the GII.17 genotype (125).…”
Section: Humoral Immune Responsementioning
confidence: 99%